O ensino de língua estrangeira sob o viés da teoria das operações predicativas e enunciativas: um estudo dos verbos frasais do inglês - Passarelli, João Daniel França (2020)
This work’s aim is to analyze the intra and interlinguistic translation processes in teaching and learning English as a foreign language (LE) and Portuguese as mother tongue (LM). Using Antoine Culioli’s Theory of Predictive and Enunciative Operations (TPEO) as theoretical foundation, we start from the premise that language is by nature a dialogic activity that is constituted by a continuous process of translation. This study proposal confronts two teaching methodologies, an instrumental one, the most common in language teaching which, basically, takes native languages as objects of observation, disarticulating them from language, a fact that implies a notion of translation based on the linguistic system. The other methodology, supported by the author, is interactional / dialogical. Using TPEO’s principles, it demonstrates how this approach can be applied to foreign language teaching. To do so, we focus English phrasal verbs – a very troublesome issue for nonnative students because of their traits that are specifically typical of the English language. Based on an enunciative perspective, we will discuss the functioning of these structures as well as the approaches to teaching them. To support that discussion, we use a corpus made of twenty sentences from various sources such as films, songs, international newspapers, dictionaries and textbooks.